MARKETING STRATEGY ANALYSIS TO INCREASE COMPETITIVENESS IN NATIONAL SHIP DESIGN INDUSTRY - Herwanzah, Fachrul; Wijaya, Sagitha Devina; Nuringtyas, Rydho Jalu (PEOPLE: International Journal of Social Sciences, 2019)
The increasingly fierce competition in the era of globalization has a considerable influence on marketing and fosters new challenges in today’s marketing functions. Business people are required to be able to understand how developments around the world can affect the domestic market and the opportunity to find new innovations, without exception the shipping design industry. The competitiveness of the national shipping design industry is also influenced by industrial competitiveness and the competitiveness of similar business actors, so that plans for developing the ship design industry must be analyzed comprehensively and accompanied by strategic steps in order to be able to run a sustainable business. Problems related to general aspects that influence the ship design industry business require special strategic formulations. Diamond model from Hambrick (2001) is considered to be able to answer the problem because it includes a series of strategic formulations, namely in helping answer questions about what strategies a company / organization needs to do in the future. The results of the formulation using this diamond model are several proposed strategies that are classified into several aspects, namely arena, vehicles, differentiations, staging, and economic logic.